Cell therapy with placenta-derived mesenchymal stem cells for secondary progressive multiple sclerosis patients in a phase 1 clinical trial - Ameneh Shokati; Mohsen Nikbakht; Mohammad Ali Sahraian; Roghayyeh Saeedi; Elnaz Asadollahzadeh; Nasim Rezaeimanesh; Bahram Chahardouli; Zeinab Gharaylou; Seyed Asadollah Mousavi; Jafar Ai; Abdorreza Naser Moghadasi (Scientific Reports)
Abstract Mesenchymal stem cell (MSC) has attracted significant attention in clinical research due to their immunomodulatory properties and potential to reduce inflammation in autoimmune disorders, such as multiple sclerosis (MS). This study evaluates the safety and feasibility of placenta-derived MSCs (PLMSCs) in five participants with secondary-progressive multiple sclerosis (SPMS). The primary outcomes focused on safety and tolerability, assessed through adverse event monitoring over six months. Secondary exploratory outcomes included clinical, imaging, and immunological measures. Patients underwent baseline evaluations and follow-up assessments comprising cognitive and psychological assessments, expanded disability status scale (EDSS), clinical signs, diffusion tensor imaging (DTI), functional MRI (fMRI), cytokine levels (IL-10, IL-6, IL-17, TNFα), and CD20/CD19 B cell marker analysis. No serious complications were noted, except for temporary headache in two patients, which was resolved with tablet. Results demonstrated sustained improvements in clinical outcomes, as indicated by significant reductions in EDSS scores (P < 0.0001), cognitive and psychological assessments, and radial diffusivity (RD) indices (P = 0.0186) in DTI metrics over six months. Furthermore, fMRI analysis showed significant enhancements in brain connectivity and cognitive function. Immunologically, CD20/CD19 B cell markers decreased significantly (P = 0.0077), and anti-inflammatory cytokine IL-10 increased alongside reductions in pro-inflammatory TNFα, IL-6, and IL-17 (P < 0.0001) three months post-therapy. These findings suggest PLMSC transplantation is safe and feasible in SPMS patients. While exploratory outcomes indicate potential clinical and immunological benefits, this phase 1 trial was not designed to assess efficacy. Larger, controlled phase II trials are warranted to validate these preliminary observations and investigate PLMSCs’ therapeutic potential in MS.